Relationship between Characteristics and Left-Handed among Gifted and Talented Muslim Students - Norazlina Subani; Nayli Nabihah Khairul Bahari; Nur Aminah Mohd Tahir (Semarak Ilmu Publishing, 2026)
Non-Indexed Publication